2006
DOI: 10.1007/s00464-005-0357-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic mesh hiatoplasty for paraesophageal hernias and fundoplications

Abstract: The current data tend to support the use of prosthetic materials for hiatal repair in both routine LF and the repair of large PEHs. Longer and more stringent follow-up evaluation is necessary to delineate better the safety profile of mesh hiatoplasty. Future randomized trials are needed to confirm that mesh repair is superior to simple crural closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 44 publications
0
64
0
7
Order By: Relevance
“…Although the associated incidence has been reported to be as low as 0-0.49%, operative management may be complex and often requires open surgery, gastrectomy, and/or esophagectomy [24,32]. No risk factors for mesh erosion have been identified to date, while PP meshes are considered to be the most irritative to the exposed esophageal tissue.…”
Section: Discussionmentioning
confidence: 96%
“…Although the associated incidence has been reported to be as low as 0-0.49%, operative management may be complex and often requires open surgery, gastrectomy, and/or esophagectomy [24,32]. No risk factors for mesh erosion have been identified to date, while PP meshes are considered to be the most irritative to the exposed esophageal tissue.…”
Section: Discussionmentioning
confidence: 96%
“…Some authors state that mesh repair should be reserved for cases where primary crural repair is not possible, but others advocate a more liberal approach. [4,5] There are some reports which state that intraoperative measuring of the hiatal surface area may help in the patient selection process and decrease the incidence of recurrence. [6] The overall impression is that mesh closure can be performed with few complications which usually require no secondary surgical intervention, but there are situations resulting in the erosion of prosthetic material which necessitate esophagectomies and gastrectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have already demonstrated that the use of mesh lowers the rates of recurrence, it is the possibility of complications what we have do pay attention to 1,4,7,8,9,12 . In our series with a long follow-up period, we found no complications related to the use of a mesh, even in those patients with recurrence.…”
Section: Frantzides and Carlsonmentioning
confidence: 95%
“…A comprehensive review of the literature regarding the use of prosthesis in the hiatus (1,368 patients) was published recently by Johnson et al 12 . One must consider the fact that the authors combine studies with different types of prostheses (PTFE, polypropylene, organic), shapes (rectangular, circular, "U-shaped"), application techniques (onlay or interposed between the pillars) and indication (routine in simple hernias and large paraesophageal hernias).…”
Section: Introductionmentioning
confidence: 99%